Recent Advances in Computational Epidemiology - Madhav Marathe; Naren Ramakrishnan (2013)
Public health epidemiology aims to understand the spatiotemporal spread of diseases and to develop methods to control such spread. Computational epidemiology has become increasingly multidisciplinary and has led to novel computational methods for understanding and controlling spatiotemporal disease spread. Recent advances focus specifically on modeling, data mining, and inferential and planning questions.